PENINGKATAN KESADARAN HUKUM PENGURUS KOPERASI MERAH PUTIH MELALUI MODEL PENYULUHAN PARTISIPATIF BERBASIS AKOSA DI KAMPUNG SENTRA WISATA CIBADUYUT - Irma Rachmawati Maruf; Tuti Rastuti; Sandra Novendra; Siti Sundari (LPPM Institut Pendidikan Nusantara Global, 2025)
The Merah Putih Cooperative (KMP) program is a government initiative aimed at achieving national economic equality in accordance with the mandate of Article 33 of the 1945 Constitution. However, in its implementation in the field, this program still faces various obstacles, mainly due to the accelerated establishment of institutions and limited human resource capacity. Many cooperative administrators and supervisors do not yet have an adequate understanding of the principles of cooperative law and the responsibilities attached to their positions as stipulated in the law. To overcome this problem, legal counseling activities are carried out using the participatory legal education approach based on the AKOSA (Alami–Kemukakan–Olah–Simpulkan–Aplikasikan) model. Through these five stages, participants were invited to identify actual legal issues in cooperatives, discuss their field experiences, analyze them based on legal provisions, draw conclusions together, and apply them through the practice of drafting Bylaws (ART) and simulating minutes of the Annual Member Meeting (RAT). The results of the activity showed a significant increase in participants' legal knowledge and skills, with the effectiveness of participatory learning reaching a level of practical significance (p < 0.05). A total of 92% of participants stated that this activity was relevant to the needs of cooperatives, and 87% wanted ongoing legal assistance. Qualitatively, this activity also showed a shift in legal culture from compliance-based to participatory-based governance, in which administrators and supervisors not only comply with the rules but also internalize legal values as institutional ethical guidelines.